Attachment, Communication, and Relationship Functioning Among College Student Veterans and Nonveterans. Issue 2 (6th July 2019) - Riggs, Shelley A.; Carver, Kellye S.; Romero, Daniel; Morissette, Sandra B.; Wilson, Jamie; Campbell, Robyn; McGuffin, James
Abstract : This study examined attachment processes of college student veterans and nonveterans and further examined how veteran status and attachment style directly and indirectly predict relationship functioning. Results indicated that student veterans were more often dismissing in their attachment style but less often preoccupied than nonveteran students. Veteran status moderated the association between attachment style and dyadic consensus. The contributions of attachment and communication processes to overall relationship adjustment differed for student veterans and nonveterans.